MICROORGANISMS FROM HANDS OF TRADITIONAL CHINESE MEDICAL DOCTORS IN A CENTRAL HOSPITAL ENVIRONMENT - Sun, Ye; Yu, LiXiang; Sun, Min; Tong, YanQing (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: In a central hospital, the heavy clinical workload makes one to overlook its hazard to health and can to a large extent promote the transmission of pathogenic microorganisms. It is not uncommon however, to observe practices that deviate from normal standards of hygiene. Hand contact between doctors of TCM and patients may lead to nosocomial infections. Materials and Methods: Samples were sourced and collected from hands of TCM doctors in a central hospital. The fungal isolates were identified by colonial morphology and microscopic examination. Sensitivity test were performed on each of the identified isolates using the Multiple Disc Diffusion method. Results: A total of 265 samples were collected from the fingers, palm and back of hands of TCM doctors. Seven organisms were isolated, with S. aureus being the most common bacterium with frequency of 55.9% in the hospital environment. Other bacteria isolated included P. aeruginosa, E. coli and K. aerogenes. S. cerevisae was the most common fungus isolated with frequency of 61.8%. Fungi isolated included P. chrysogenum and A. niger. Conclusion: The study showed clearly that hand contact between TCM doctors and patients may lead to infection of exposed susceptible patients. Results of antibiotic susceptibility pattern show that isolates in this study are mostly resistant to augmentin and most antibiotics of old generation, while gentamycin and pefloxacin were highly active against most of isolates. Considering the possibility of transmission of contamination, special attention should be directed towards disinfection of TCM doctors’ hands.